Health education interventions to minimize defaulting of leprosy patients on multidrug therapy - Ong, Rafaelita A. (1996)
The study was undertaken to determine the efficacy of a health education intervention package in effecting two treatment behaviours, medication-taking and appointment-keeping, among defaulting multibacillary cases to multidrug therapy (MDT).Sixty compliers and sixteen defaulters to MDT under the Department of Health Leprosy Control Program (National Capital Region) were involved. The study was divided into two phases. Phase I involved baseline data survey to identify determinants of the compliant behaviour and to come up with a predictive model to the compliant behaviour. Phase II included pre-intervention activities and implementation of the educational package consisting of training of nurses and midwives, patient counselling, family member counselling, and group session.Chi square tests revealed significant difference between the compliers and defaulters in twenty-three variables.T-test results showed association of four constructs (KABP, behavioural intentions, accessibility and personal experience with treatment regimen) to the compliant behaviour.Stratified analysis suggests strong association of behavioural intentions and personal experience with treatment regimen to the compliant behaviour.The educational intervention had elicited a compliance rate of 14.3, 71.4and 57.1at the first, second and third observations, respectively.Findings of the study revealed some implications in the implementation of DOH program acitivities /strategies for the control of leprosy.Cost-effectiveness study to test efficacy of patient counsellung and testing of the same educational package to bigger sample size are research areas recommended by the study.